Strategi Pengembangan Usaha Melalui Kualitas Layanan Dan Penetapan Harga Pada Toko Model Bridgestone - Anisa Oktaviani; Yolce Oktiara; Nurhalimah (CV. ITTC INDONESIA, 2024)
Bridgestone Model Stores must take strategic steps in the development of their business to stay competitive and retain loyal customers in the midst of increasingly fierce competition in the market. Customers who are satisfied with good service will prefer to shop again. Employees of this store should be trained to provide friendly, fast, and professional service to each customer.